Small businesses and liquidity constraints in financing business investment - Chow, Clement Kong-Wing; Fung, Michael Ka Yiu (Journal of Business Venturing, 2000)
When firms experience financial hierarchy, external finance, if at all available, is substantially more expensive than internal finance. Factors such as transaction costs, agency problem, and asymmetric information have created such a hierarchy. Stiglitz and Weiss (1981) argue that asymmetric information between firms and potential suppliers of external finance creates adverse selection and moral hazard problems in the credit market in developed market economies. This problem of a higher cost of external finance is commonly thought to be more serious for small firms because they are more disadvantaged than their larger counterparts in accessing external finance due to several factors: (1) Public information on small firms is generally not available and leads to the even greater problem of asymmetric information, i.e., more severe adverse selection and moral hazard problems. These information problems have excluded small firms from bond and share markets. (2) Due to the lack of available means of external finance, small firms rely more heavily on bank loans than their larger counterparts. In addition, as small firms are more interested in cultivating stable relationships with a few banks in order to secure a stable supply of credit, these banks become virtual monopolies by lending to small businesses and exercise their market power in lending to small firms. Most of existing research considers only small firms in market economies; little research has been done to understand the relationship between firm size and investment financing in any economy in transition. This paper makes a contribution to the literature by studying the relationship between firm size and liquidity constraints by using a firm level data of manufacturing enterprises in Shanghai during the period of 1989–1992. We consider whether small manufacturing firms in Shanghai are constrained by the availability of liquidity compared with their larger counterparts when they are financing their fixed investment. In a transforming economy such as China (or other similar transition economies), external finance relies heavily on loans from banks that are fully owned by the state. Due to historical reasons, allocations of credit are always biased in favor of state-owned enterprises. Such a `lending bias' imposes an extra cost on small Chinese enterprises in financing investment as the majority of them are not state-owned. In such an environment, our empirical results show that small manufacturing firms in Shanghai are actually less liquidity-constrained than their larger counterparts in financing their fixed investment. This surprising result is rather different from what people normally predict based on the experience in market economies. We suggest three possible explanations for this peculiar finding: (1) The composition of various firm size classes plays an important role in explaining the result: Non-state enterprises which are fast growing and efficient dominate the small firm classes. Their successes in the markets helps them to generate enough internal funds to smooth their investment over time. (2) The presence of heavy indebtedness of large state-owned enterprises may deprive them of sufficient cash available for investment decision. Given that state-owned enterprises have been making heavy losses, the central and regional governments have a liquidity problem in satisfying their huge liquidity demands. (3) Small enterprises in non-state sectors can rely on the informal credit market to obtain funds for investment although they are excluded from the state banking system. However, the further trade liberalization in terms of eliminating tariffs and quotas caused by China's bid of joining the WTO will erode the profits of these small enterprises as imported goods will be supplied at lower prices. In addition, further reforms in financial sectors may also affect the supply of external finance to small enterprises in nonstate sectors. The consequence may lead to a tight liquidity constraint for small enterprises in China.